PENGEMBANGAN LEMBAR KEGIATAN PESERTA DIDIK (LKPD) BERBASIS PROBLEM BASED LEARNING (PBL) PADA MATA PELAJARAN KIMIA SMA POKOK BAHASAN HIDROKARBON - Surya, Wisnu Prammana; Holiwarni, Betty (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This Research aims to develop Student Worksheet Based on Problem Based Learning in Hydrocarbon of Chemistry in Senior High School Subject in terms of valid based on the feasibility aspect of content, language, serve and graphic. This type of research is research and development (R and D) with reference to the development process of 4-D model. The subject of this research is student worksheet based on problem based learning. Instrument of data collection are validation and data collection technique given by three validators. Analysis of data obtained by the validity of aspect of content is 92.5% with valid category, the validity of aspect of language is 95% with valid category, the validity of aspect of serve is 90% with valid category and validity of aspect of graphic is 93.75% with valid category. Based on the results of data analysis can be concluded that student worksheet based on problem based learning declared valid and can be used in Senior High School.Key Words: Hydrocarbon, Problem Based Learning, Student Worksheet